Daniel, John & Uvalić‐Trumbić, Stamenka ed (2013) A guide to quality in online learning. Contact North (Ontario, Canada) No isbn 28 pp Free download http://www.contactnorth.ca/tips‐tools/guide‐quality‐online‐learning. (January 2014) - Smyth, Robyn
Summary This guide to the quality of online learning is an extremely readable and useful publication which anyone interested in the field should read in order to refresh or enhance their understanding of this complex and evolving learning environment. This is a highly recommended resource for all educators and managers of learning and teaching. If the content of this book is likely to be at all relevant to you, I recommend you download your own copy. Robyn Smyth